(untitled) (Journal of the College of Education for Women, 2021)
The present paper focuses on examining the style of both the civilized dialogue of Prophet Hud (PBUH) in the Glorious Qur’an, and the debated dialogue of Aad’s people. The study consists of an introduction which shows the importance of the civilized dialogue and its significant impact on containing, accepting, and persuading the other in peaceful ways without intolerance and violence. Then, the conditions and techniques of the civilized dialogue and its types have been mentioned. This is followed by the practical side of the study, which involves examining stylistically the techniques used in Hud’s (PBUH) civilized dialogue to be invested later in people’s future conversations. It is also concerned with investigating stylistically Aad’s debated dialogue to avoid the techniques used in them in any future conversations. The research finally highlighted a number of conclusions, such as: The civilized dialogue is a persistent human need, especially with the increasing use of the debated dialogue which has led to devastating results at a global level. Moreover, Hud’s dialogue with his people was characterized by being civilized. Through which, he tried to contain, accept and persuade the other to the path of goodness and faith using various linguistic styles. The style of the Holly Quraan has stated through the transmitted Aad’s dialogues with Hud (PBUH) that Aad’s dialogues were debated and characterized by violence, threat, intimidation, and false accusation. Such a style was used by Aad people to stop Hud from promoting his invitation.